Meningkatkan Literasi Kesehatan Mental sebagai Upaya Deteksi Dini Gangguan Psikologis di Desa Setia Mekar, Bekasi - Merida, Sarita Candra; Ramadhani, Faizal; Delciello, Maria; Zikri, Muhammad Nur; Athallah, Naufal Labib; Setawati, Nur; Salsabila, Oskanita; Zaliha, Putri; Meliani , Sinta; Ariantono, Wahyu (Devotion : Jurnal Pengabdian Psikologi, 2024)
Based on geographic location, the village of Setia Mekar borders Bekasi City, which means that access to new information is easy to obtain. In fact, based on the result of the assessment carried out, there are still limitations to literacy within the community, especially in literacy that related to mental health. Therefore, the aim of this activity is to increase mental health literacy in the community of Setia Mekar Village. Individuals with good mental health literacy, can carry out early detection of psychological disorders. The method that used to increase mental health literacy is by providing psychoeducation in the village of Setia Mekar. Before the intervention is given, an assessment is first conducted to determine the appropriate psychoeducation method. The results obtained through this psychoeducation activity show that residents become more aware about psychological disorders, the characteristics or symptoms, casual factors, and treatment of psychological disorders themselves.